DEVELOPMENT OF LEGAL BASIS AND INSTITUTIONS OF STATE-PRIVATE PARTNERSHIP IN THE RUSSIAN FEDERATION - Larissa R. Kotova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article through analyzing federal and regional law in the field of state-private partnership shows contradictions and problems existing in the legal field, which prevent the development of this phenomenon in Russia, such as the absence of clear guarantees minimizing risks for business; antagonism between concessional legislation and laws about investment activity; declarative nature of many regional laws, etc. The author assesses the efficiency of such finance institutions of state-private partnership as the Investment Fund and Vnesheconombank. Principle investment risks in Russia were identified as they can influence the development of highly technological industries providing growth of Russian economy.